Geomorphic and land cover identification of dust sources in the eastern Great Basin of Utah, U.S.A - Hahnenberger, Maura; Nicoll, Kathleen (Geomorphology (Amsterdam, Netherlands), 2014)
This study identifies anthropogenically disturbed areas and barren playa surfaces as the two primary dust source types that repeatedly contribute to dust storm events in the eastern Great Basin of western Utah, U.S.A. This semi-arid desert region is an important contributor to dust production in North America, with this study being the first to specifically identify and characterize regional dust sources. From 2004 to 2010, a total of 51dust event days (DEDs) affected the air quality in Salt Lake City, UT. MODIS satellite imagery during 16 of these DEDs was analyzed to identify dust plumes, and assess the characteristics of dust source areas. A total of 168 plumes were identified, and showed mobilization of dust from Quaternary deposits located within the Bonneville Basin. This analysis identifies 4 major and 5 secondary source areas for dust in this region, which produce dust primarily during the spring and fall months and during moderate or greater drought conditions, with a Palmer Drought Index (PDI) of −2 or less. The largest number of observed dust plumes (~60% of all plumes) originated from playas (ephemeral lakes) and are classified as barren land cover with a silty clay soil sediment surface. Playa surfaces in this region undergo numerous recurrent anthropogenic disturbances, including military operations and anthropogenic water withdrawal. Anthropogenic disturbance is necessary to produce dust from the vegetated landscape in the eastern Great Basin, as evidenced by the new dust source active from 2008 to 2010 in the area burned by the 2007 Milford Flat Fire; this fire was the largest in Utah's history due to extensive cover of invasive cheatgrass (Bromus tectorum) along with drought conditions. However, dust mobilization from the Milford Flat Burned Area was limited to regions that had been significantly disturbed by post-fire land management techniques that consisted of seeding, followed by chaining or tilling of the soil. Dust storms in the eastern Great Basin negatively impact air quality and transportation in the populated regions of Utah; this study details an improved forecasting protocol for dust storm events that will benefit transportation planning and improve public health. •We analyzed dust sources in the eastern Great Basin over seven years using MODIS.•Eastern Great Basin dust sources are playas and disturbed regions.•Most dust sources are subject to anthropogenic impacts.•Drought increases dust production both from disturbed areas and playas.